Keeping Pace: A Practitioner-Focused Review of Pacing Strategies in Running. Issue 1 (February 2020) - Pryor, J. Luke; Johnson, Evan C.; Yoder, Hillary A.; Looney, David P.
Abstract : ABSTRACT: The purposeful distribution of speed, power, or energy is termed as the pacing or pacing strategy and is recognized as a key determinant in optimal run performance. There is no agreement on the best pacing strategy for all runners and race types. Thus, the challenge posed to runners and practitioners is pacing strategy selection and in-race adherence. This review briefly discusses pacing strategy types and selection considerations. More importantly, we overview factors influencing pacing and translate key findings from research into useable evidence-based recommendations for pacing strategy preparation and adherence during competition.